Republic of Belarus : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2019)
This Selected Issues paper takes stock of the current level of dollarization, both in historic and international perspective. By looking at recent measures and international best practice, it draws some recommendations for a successful de-dollarization framework. Belarus has a high level of loan and deposit dollarization as a result of repeated external crises and hyperinflation. Dollarization in Belarus is much higher than many other countries, accounting for various drivers of dollarization. Dollarization has been decreasing but it is still higher than a decade ago. The authorities have been taking welcome steps to liberalize the foreign exchange (FX) market, such as, for example, eliminating the FX surrender requirement and easing the registration procedure for FX transactions. An overarching and publicly communicated national strategy to de-dollarize the economy is a missing piece of the puzzle. Such a strategy would be an important signaling and commitment device and would help educate borrowers about the risks (private and social) of FX borrowing. The strategy would contain an operational roadmap that would also ensure the coherence of existing policies, and coordinate policy and operational steps.